Pengembangan Bahan Ajar Mata Pelajaran Pendidikan Agama Islam Oleh Tutor di Pendidikan Non Formal - Muhammad Faiq Hirzulloh; Suad Fikriawan; Diyan Putri Ayu (Social Science Academic, 2024)
Merdeka Curriculum emerged as an effort to create interactive, efficient, and certainly more productive learning. This curriculum has many benefits for tutors, one of which is that tutors can have more freedom to create teaching materials so that students can develop optimally. The focus of this research is the development of PAI teaching materials by tutors at PKBM Daarul Ahkaam. This research discusses the objective condition of PAI teaching materials, the problems faced by PAI Tutors, and the steps taken by PAI Tutors to develop the teaching materials. The approach used in this research is qualitative with the type of case study. The results obtained are the objective conditions of teaching materials in accordance with Merdeka Curriculum, Tutors are responsible for preparing lesson plans while the principal PAI material that has been determined is developed by the Tutors themselves. The problems faced by Tutors are determining teaching materials that are relevant to the competency standards and basic competencies, lack of infrastructure, and problems that arise from students who do not understand the material coupled with limited teaching material sources. The steps in developing teaching materials are relevant to process standards, Tutors have selected teaching materials in accordance with competency standards, used varied strategies and applied learning evaluations in accordance with the independent curriculum.